Price smoking participation elasticity in Colombia: estimates by age and socioeconomic level (2020)
BACKGROUND: Tobacco prevalence in Colombia is small compared with other Latin America despite the nation's tobacco taxes being among the lowest in the region. However, tobacco taxes have increased several times during the last decade, and large increases in 2010 and 2016 impacted consumer prices.OBJECTIVE: This paper aims to estimate the price smoking participation elasticity (PPE) in Colombia, with specific reference to regional increases in consumer prices after 2010 tax policy changes.METHODS: The PPE is computed using logistic regression based on individual-level data from the National Psychoactive Substances Consumption Survey for 2008 and 2013. Our specific focus is state-level variation in Colombian cigarette prices between 2008 and 2013 induced by the tax hike in 2010.RESULTS: The estimated PPE in Colombia is around -0.66 (p value=0.046). We find almost no differences across socioeconomic level, but price sensitivity was greater for women than men, and for relatively older individuals (ages 51-64).CONCLUSIONS: PPE for Colombia is above estimates for comparable middle-income countries such as Mexico. As a result, current estimates for health gains of tax policies are likely to be underestimated. Moreover, in contrast with the literature, we find that the PPE for the youth (?25 years) is lower than older age groups, and there is no evidence of a prominent socio-economic status (SES) gradient.